Pengaruh Green Entrepreneurial Orientation terhadap Perilaku Green Economy melalui Program Kewirausahaan pada Mahasiswa Fakultas Ekonomi dan Bisnis - Mursyidah, Desta Sulaesih; Asri, Yoana Nurul; Phety, Debora Tri Oktarina; Setiawan, llham (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
Entrepreneurship education in higher education is related to building entrepreneurial character, an entrepreneurial mindset, and entrepreneurial behavior that is always creative and innovative. The aim of this research is to see the correlation between green entrepreneurial orientation and the green economy through entrepreneurship programs among students at the Faculty of Economics and Business. This research involved 56 respondents from the Faculty of Economics and Business in Bandung using convenience sampling. The results show that there is a positive correlation between green entrepreneurial orientation and green economic behavior among students, especially as an output for Entrepreneurship courses, especially those taking part in the MBKM Entrepreneurship program. Apart from that, respondents appear to have a strong desire to be involved as environmentally friendly entrepreneurs, however, after financial cash reaches stability or reaches BEP (Break Even Point) where the profit results are equivalent to the capital spent.